Roles of Oxidative Stress in Synaptic Dysfunction and Neuronal Cell Death in Alzheimer's Disease - Germán Plascencia-Villa; George Perry (MDPI AG, 2023)
Alzheimer's disease (AD) is a brain disorder that progressively undermines memory and thinking skills by affecting the hippocampus and entorhinal cortex. The main histopathological hallmarks of AD are the presence of abnormal protein aggregates (Aβ and tau), synaptic dysfunction, aberrant proteostasis, cytoskeletal abnormalities, altered energy homeostasis, DNA and RNA defects, inflammation, and neuronal cell death. However, oxidative stress or oxidative damage is also evident and commonly overlooked or considered a consequence of the advancement of dementia symptoms. The control or onset of oxidative stress is linked to the activity of the amyloid-β peptide, which may serve as both antioxidant and pro-oxidant molecules. Furthermore, oxidative stress is correlated with oxidative damage to proteins, nucleic acids, and lipids in vulnerable cell populations, which ultimately lead to neuronal death through different molecular mechanisms. By recognizing oxidative stress as an integral feature of AD, alternative therapeutic or preventive interventions are developed and tested as potential or complementary therapies for this devastating neurodegenerative disease.